How digital technologies enhance competitiveness in manufacturing SMEs - Silva, A. da.; Duarte de Almeida, I.; Dionísio, A.; Rabadão, C.; Capela, C. (Journal of Innovation and Entrepreneurship, 2025)
This study examines how digital technologies influence the competitiveness of manufacturing small- and medium-sized enterprises (SMEs), with a focus on labor productivity and export performance. Using a sample of 669 firms in the Portuguese ornamental stone sector, a framework was applied to evaluate five levels of digital maturity through a quantitative approach. This analysis covers five years after the investment and combines digital profiling with scenario-based forecasts. Results, presented in figures and tables, indicate a positive link between digital maturity and firm performance, with higher digitalisation levels correlating with increased productivity and export efficiency. For example, the most digitally mature firms experienced labor productivity increase significantly, and their digital investments yielded returns very handsomely for every euro invested. These findings, while illustrative, depend on specific contextual factors and assume ongoing digital adoption. This study offers a replicable model for evaluating digital revolution in traditional industries, supporting SME policy development and strategic planning.